From Patient Safety Culture to Patient Safety Competency: Authentic Leadership and Psychological Safety as Key Pathways - Ji Hee Yang; Eunyoung Hong (JONA: The Journal of Nursing Administration, 2026)
Objective: To examine a serial mediation model linking patient safety culture to patient safety competency through authentic leadership and psychological safety among general hospital nurses. Background: The mechanism by which patient safety culture influences individual competency remains unclear. Methods: The study applied a cross-sectional survey research design of 201 nurses from 3 South Korean general hospitals. Data were analyzed using PROCESS Model 6. Results: Patient safety culture predicted authentic leadership (β=0.61), psychological safety (β=0.45), and competency (β=0.16). Authentic leadership predicted psychological safety (β=0.31) and competency (β=0.25). Psychological safety predicted competency (β=0.30; all P